Haikyu!! 3-in-1 edition. 7-8-9 - Furudate, Haruichi, 1983- (Shonen Jump manga., 2024)
Ever since he saw the legendary player known as "the Little Giant" compete at the national volleyball finals, Shoyo Hinata has been aiming to be the best volleyball player ever! Who says you need to be tall to play volleyball when you can jump higher than anyone else? The Inter-High match between Karasuno and Aoba Johsai continues. Star setter Tohru Oikawa has figured out the secret behind Kageyama's and Hinata's quick sets and has them on the ropes! When Kageyama loses his cool, he ends up getting benched and is subbed out by none other than third-year Koushi Sugawara. And Tadashi Yamaguchi is brought out as a pinch server! Will Karasuno's new approach be enough for them to seize control of the game and win?